Usage of ICAR e-learning Portal Among Students of North East India: A Pilot Study - D. K. Pandey , H. K. De; A. D. Upadhayay (Indian Journal of Extension Education, 2017)
The aim of this study was to analyze the usage of ICAR e-learning portal and other online resources among students of North east India. A well structured questionnaire was administered to 199 students and faculty of agriculture colleges. Source of accessing internet; time spent on internet; use of digital academic resources and its benefits; frequency of visiting portal etc. were studied. Suggestions were sought on improving the portal. Around 85 per cent of the respondents reported that access to internet improves learning and the contents were found useful by around 80 per cent of the respondents. Extent of use of the portal by the academic fraternity is poor as only 18.56 per cent of them downloaded any resource from the portal. Majority (51.71%) of the respondents suggested adding Power Point presentations and videos in support of the subject contents. Lack of strategic planning and vision was the major barrier in e-learning implementation as perceived by teachers. Development time of e-course contents was perceived as second important barrier. Lack of training in technological developments and support were also identified as constraints by the teachers.